(3HQO GdJTOjO aj eSCdI GdJbdjOs - (3CMeO Hf eHGQc GdSLdeGSj GddeWjs
(3ChdgG (B:s
(3GdMeO ddg hMOg hUdi Gddg Ydi eMeO hHYO agPg MQha jSjQI ajgG Ydhe ZRjQI SejJgG HQO GdJTOjO ai eSCdI GdJbdjO s
(3BNQgG (B:s
(3hTcQhG ajg ef MSf GdJfHjg hUdi Gddg Ydi SjOfG eMeO hBdg aGPcQg GdPGcQhf s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(279 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds